The Effects of Social Capital on the Self Reliance of Posyandu - Dian Arie Sushanty; Mochammad Bagus Qomarrudin; Ira Nurmala (Health Notions, 2018)
Posyandu (integrated health service post) refers to the activities of empowering the community in healthcare. The problem that appears recently is the low functions and the performance of Posyandu seen from the low achievements made by Posyandu Mandiri (self-reliant Posyandu). This observational study done by using cross sectional design. 45 Posyandu were taken as the samples in Bontang, East Kalimantan. The community taken as the respondents was the cadres, the public figures, and the mothers/families having babies and children under five. The statistic tests used in this study were linear regression test and logistic regression test. The results of this study showed that social capital have brought effects to the community participation, not only to the cadres, the public figures, but also the mothers/families having babies and children under five. The community participation in healthcare has affected the achievement of Posyandu to reach self reliance. The social capital has been proven to bring effects to self reliance of Posyandu through the community participation. The revitalization of Posyandu must consistently involve the community participation by reinforcing the available social capital. Keywords: Community participation, Self reliance of Posyandu, Social capital